Preparation of hydroxyl and (3‐aminopropyl)triethoxysilane functionalized multiwall carbon nanotubes for use as conductive fillers in the polyurethane composite. Issue 4 (17th May 2016) - Li, Shasha; Wang, Zhongde; Jia, Jinlan; Hou, Caiying; Hao, Xiaogang; Zhang, Hui
Abstract : A new method has been developed to prepare hydroxyl‐functionalized multiwall carbon nanotubes (MWCNTs‐OH) and (3‐aminopropyl)triethoxysilane‐functionalized MWCNTs (MWCNTs‐APTES), which can be uniformly dispersed in solvent‐borne polyurethane (PU) to obtain the nanocomposites with enhanced mechanical, thermal, and electrical properties. Scanning electron microscope, X‐ray photoelectron spectroscopy, Fourier transform infrared spectrometer, and thermogravimetric analyzer were employed to characterize the changes in MWCNTs surface morphology and structure. The result showed that the oxidation of MWCNTs by H2 O2 in NaOH solution caused small damages to their structure, and oxygen‐containing functional groups were mainly present as hydroxyl groups, which acted as binding sites in the next silanization process. The functionalization provided MWCNTs with improved dispersibility and strong interfacial bonds in/with PU matrix, resulting in an increase in the wettability, tensile strength, hardness, storage modulus, glass transition temperature, thermal stability, and electronic conductivity of the PU composites. In comparison with the MWCNTs‐OH composites, MWCNTs‐APTES composites exhibited more enhanced above properties because hydroxyls or amines could increase the interfacial adhesion between MWCNTs and PU matrix, whereas alkyl groups of the silane are favor of increasing the filler's compatibility with polymer. At loading of 6 wt% MWCNTs, the tensile strength and electronic conductivity of MWCNTs‐OH/PU were 2.45 MPa and 1.72 S/cm, respectively, but increased to 3.45 MPa and 87 S/cm for the MWCNTs‐APETS/PU composite. POLYM. COMPOS., 39:1212–1222, 2018. © 2016 Society of Plastics Engineers